2021
DOI: 10.1002/cbdv.202100705
|View full text |Cite
|
Sign up to set email alerts
|

Digestion‐Promoting Effects and Mechanisms of Dashanzha Pill Based on Raw and Charred Crataegi Fructus

Abstract: Emerging evidence suggests that a high-fat diet (HFD) can influence endoplasmic reticulum (ER) stress and gut microbiota. Crataegi Fructus is a traditional Chinese herb widely used in formulas for dyspepsia, with Dashanzha Pill composed of raw Crataegi Fructus (DR) being a representative drug. Processing products of Crataegi Fructus, however, have a stronger pro-digestive effect, and we hypothesized that Dashanzha Pill composed of charred Crataegi Fructus (DC) is more effective. We found that the contents of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…UPLC-Q-Orbitrap HRMS has been widely used in the qualitative analysis of TCM because it provides a platform to observe fragment ions of compounds and has the advantages of high sensitivity, high-resolution, high accuracy, and a wide scanning range. The technology not only helps to solve the problem of the diversity and complexity of TCM, but also establishes a foundation for elucidating the therapeutic mechanism of TCM and the development of new drugs ( Wong et al, 2016 ; Liu et al, 2021 ). In this study, six compounds were detected only in RPS, and 10 compounds were detected only in WPS.…”
Section: Discussionmentioning
confidence: 99%
“…UPLC-Q-Orbitrap HRMS has been widely used in the qualitative analysis of TCM because it provides a platform to observe fragment ions of compounds and has the advantages of high sensitivity, high-resolution, high accuracy, and a wide scanning range. The technology not only helps to solve the problem of the diversity and complexity of TCM, but also establishes a foundation for elucidating the therapeutic mechanism of TCM and the development of new drugs ( Wong et al, 2016 ; Liu et al, 2021 ). In this study, six compounds were detected only in RPS, and 10 compounds were detected only in WPS.…”
Section: Discussionmentioning
confidence: 99%
“…The main ingredients of JWXSD are charred hawthorn and charred malt. A study has evaluated charred hawthorn outperformed raw hawthorn in relieving dyspepsia by regulating gut microbiota [31]. Evidence indicates that hawthorn decoction coupled with the odor of charred hawthorn effectively alleviates highcalorie-diet-induced dyspepsia in rats by regulating the "Brain-Gut" axis and gut ora [32].…”
Section: Discussionmentioning
confidence: 99%
“…[59][60][61] Excessive salt intake leads to changes in intestinal microbiota and promotes the activation of innate and adaptive immune systems, resulting in salt-sensitive hypertension. 62 However, only few studies have explored on the role of gastrin in the gut microbiome. One study showed that charred Crataegi fructus can promote gastrin secretion and restore the composition of disturbed intestinal microbiota to normal levels, including Bacteroides, Akkermansia, and Intestinimonas.…”
Section: Discussionmentioning
confidence: 99%